RANCANGBANGUNPROTOTYPE PANEL SURYA SEBAGAI ALAT PENGUSIR HAMA BURUNG - Waluyo, Ahmad Edi; Waluyo, M.Imha Ainun x; Jalil, Irham Abdul; Santoso, Andi; Fiati, Rina (Program Kreativitas Mahasiswa - Teknologi, 2014)
There are many ways which can be done by farmers to repel the bird pests, one of them is by using ultra sonic wave (Parcaya, 2008). Among the farmers there are some methods which are used to repel this bird pest such as by making âorang-oranganâ (puppet), banners, ringing cans, putting plastic bags ,catapult and even using air rifle. By means of this bird pest repelling device using ultra sonic wave, it will be benefit for the farmers to repel the bird pest. This device consists of several series electronic, such as solar panel, series of battery charger controller , storage batteries, series of light sensor, series of amplifier/intensifier laser IC 555 and series of ultrasonic sensor. The degree of influence of sparrow pest was decreasing by 95%. The method applied for 4 stages, namely collecting data, device design, device construction and device testing/experiment. The result of this research is solar panel prototype design as a bird pest repelling device innovation which is useful for farmers to ease the jobs. Keywords : bird pest, ultrasonic wave, farmers, solar panel, storage battery